2012
DOI: 10.1016/j.jacc.2012.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Post-Conditioning Reduces Infarct Size and Edema in Patients With ST-Segment Elevation Myocardial Infarction

Abstract: This randomized study demonstrated that post-conditioning reduced infarct size and edema in patients with reperfused STEMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
162
1
8

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 205 publications
(181 citation statements)
references
References 40 publications
7
162
1
8
Order By: Relevance
“…Improvements were seen in myocardial perfusion and functional outcomes compared with those in patients who did not undergo postconditioning. Thuny, et al 41) randomly assigned 50 patients with STEMI to either a control group or postconditioned group. Postconditioning was associated with smaller infarct size ( ; P < 0.03).…”
Section: Non-pharmacological Cardioprotectionmentioning
confidence: 99%
“…Improvements were seen in myocardial perfusion and functional outcomes compared with those in patients who did not undergo postconditioning. Thuny, et al 41) randomly assigned 50 patients with STEMI to either a control group or postconditioned group. Postconditioning was associated with smaller infarct size ( ; P < 0.03).…”
Section: Non-pharmacological Cardioprotectionmentioning
confidence: 99%
“…[1] Since Zhao et al [2] proposed the concept of ischemic post-conditioning in 2003, many studies have demonstrated that postconditioning can alleviate reperfusion injuries. [3][4][5][6] Post-conditioning must be performed strictly according to the protocols, namely post-conditioning algorithms, [7] or it will lose the cardioprotection effect. To the present, no "ideal" algorithm has been established.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the protective effect of RPostC against focal cerebral ischemia in rats was also verified [16]. However, its potential protective mechanisms have not been established.Recent developments in cardiac physiology have indicated that PostC significantly reduces infarct size and inhibits inflammation and apoptosis [17][18][19][20][21]. Zhao [22] at first documented that PostC reduced infarct size in cerebral I/R injury.…”
mentioning
confidence: 99%